KESEHATAN MENTAL DAN TINGKAT KETERGANTUNGAN ACTIVITY DAILY LIVING PADA LANSIA DENGAN PENURUNAN KEMAMPUAN KOGNITIF DI POLI GERIATRI RUMAH SAKIT TK. II UDAYANA DENPASAR - N LP Suardini Yudhawati; Silvia Intan Wardani; Ni Luh Made Asri Dewi (STIKes Maharani Malang, 2023)
Background: Various declines in function experienced by the elderly have the risk of causing various physical and mental health problems. One of the causes of the decline in the mental health of the elderly is a decrease in cognitive abilities and reduced independence of the elderly in carrying out daily activities to meet their basic needs. Purpose: this study was to determine the mental health and the level of ADL dependency in the elderly with decreased cognitive ability in the elderly. Method: Quantitative research method with a cross-sectional approach. The sample size of this study was 240 elderly who met the inclusion criteria. Result and analysis: spearman rank analysis shows p value is 0.000, so p > α. Conclusion: there is a significant relationship between mental health and the level of ADL dependency in the elderly with decreased cognitive abilities. Keywords: Activity daily living, Cognitive Ability, Mental Health, Elderly